Genotyping of Haemophilus influenzae type b in pre-vaccination era - Otsuka, Taketo; Fujii, Koyata; Okazaki, Minoru; Komiyama, Kenichi; Yoshida, Kazunaga; Ishikawa, Yukio; Zaraket, Hassan (Journal of infection and chemotherapy : official journal of the Japan Society of Chemotherapy, 2012)
Identification of Haemophilus influenzae type b (Hib) in asymptomatic carriers is critical to control the spread of disease. This study was conducted between January 2008 and August 2011 as part of a birth cohort study in Sado Island, Japan, to elucidate the prevalence of Hib and its clones in a specific region. Nasopharyngeal cultures were obtained from 349 subjects at 4-, 7-, 10-, 18-, and 36-month health checkups and analyzed for H. influenzae. The Hib and nontypeable H. influenzae detection rates ranged from 0 to 1.5% (12 isolates) and from 7.9 to 32.9%, respectively. Twelve pediatric patients diagnosed with invasive or non-invasive Hib infections during the study period were also enrolled. The Hib isolates were analyzed for carriage of the beta-lactamase gene and ftsI mutations, and multilocus sequence type (MLST, ST type). Of the 24 Hib isolates, 18 (75%) were ST54, 5 (21%) were ST190, and 1 isolate (4%) was ST95. All of the ST190 isolates were genetically beta-lactamase-negative ampicillin-susceptible isolates, while all but one of the ST54 isolates were genetically beta-lactamase-positive amoxicillin/clavulanic acid-resistant isolates. The geographic distribution of Hib isolates in the study period was scattered. There were 2 day-care cases and 1 family case of Hib infection. The ST54 and ST190 strains circulated in Sado Island and were detected in both asymptomatic carriers and patients. We note that surveillance of healthy subjects to identify Hib carriers is important to understand the transmission of Hib.